Perspectives on seagrass ecosystem services from a coastal community. (November 2019) - Ambo-Rappe, R; La Nafie, Y A.; Marimba, A A; Cullen-Unsworth, L C.; Unsworth, R K.
Abstract: Seagrasses are marine flowering plants, which form extensive meadows mostly in shallow water marine environments. They provide a wide range of ecosystem services, which can be grouped into four broad categories: provisioning (e.g. food production); regulating (e.g. controlling climate and disease); supporting (e.g. nutrient cycles and oxygenation); and cultural (e.g. spiritual and recreational benefits). These services directly or indirectly benefit humans. Seagrass have contributed to the fulfilment of human needs for a very long time, before the term "ecosystem services" was coined. However, there is a lack of knowledge regarding public awareness on seagrasses and the benefits they provide. In this study, we conducted a workshop in Selayar Archipelago, South Sulawesi, Indonesia, an area with extensive seagrass meadows. The workshop focussed on seagrass meadows in the context of coastal community livelihood-related activities. The 50 workshop participants came from a variety of backgrounds, mostly related to the marine and fisheries sector (e.g. fishermen, vocational high school students, conservation agency staff, district government fisheries officers, and fisheries extension staff). The workshop revealed that many marine and fisheries stakeholders have a high level of awareness regarding seagrasses and the basic ecosystem services they provide. Some key points were identified from the workshop: 1) seagrasses were recognised as a resource; 2) the most and least frequently mentioned ecosystem service types mentioned were "provisioning" and "cultural", respectively; 3) threats to seagrass meadows were identified and practical recommendations to minimize the threats were formulated.